2012
DOI: 10.1213/ane.0b013e31825d638c
|View full text |Cite
|
Sign up to set email alerts
|

A Vibro-Tactile Display for Clinical Monitoring

Abstract: Anesthesiologists found a vibro-tactile belt to be wearable and usable and could accurately decode vibro-tactile messages in a real-time clinical environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 18 publications
2
20
0
Order By: Relevance
“…The PSSUQ has been used in healthcare to evaluate clinical monitoring [46], anesthesia [47], as well as telerehabilitation systems [48]. PSSUQ scores range from 1 to 7, with lower scores representing better perceived system usability.…”
Section: Methodsmentioning
confidence: 99%
“…The PSSUQ has been used in healthcare to evaluate clinical monitoring [46], anesthesia [47], as well as telerehabilitation systems [48]. PSSUQ scores range from 1 to 7, with lower scores representing better perceived system usability.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to simplifying the visual presentation of monitoring information, there have been other attempts to improve users' situation awareness. One study, e.g., analyzed a vibro-tactile-belt display, which mapped and converted monitoring parameters and their changings into stimulation patterns [19]. Another study, which evaluated the potential of a head-worn display for multiple patient monitoring in supervising anesthetists found that the device improved situation awareness [20].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to simplifying the presentation of monitoring information, as Visual Patient Technology does, there have been other attempts to improve users' situation awareness. One study, e.g., analyzed a vibro-tactile-belt display, which mapped and converted monitoring parameters and their changings into stimulation patterns [28]. Another study, which evaluated the potential of a head-worn display for multiple patient monitoring in supervising anesthetists, found improved situation awareness [29].…”
Section: Discussionmentioning
confidence: 99%